2017
DOI: 10.1111/myc.12623
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characteristics of Candida albicans isolates from bloodstream and mucosal infections

Abstract: The interaction of Candida albicans with the host is of a complex nature involving fungal factors and host's response. In this study, we concentrated on the phenotypic expression of virulence attributes and genotypic characteristics of C. albicans isolates from two distinct clinical entities of candidiasis-blood stream and vaginal infections, and the possible role of these factors. Hence, we conducted a comparative in vitro assessment of virulence characteristics, including adhesion to epithelial cells and HaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Different isolates and strains of C. albicans vary significantly in the interactions that they establish with the host mucosa (Mandelblat et al, 2017;Schönherr et al, 2017). Experiments in mice have shown, for example, that independently of the source (e.g., bloodstream, OPC, or VVC), some C. albicans isolates can persist for a long time in the tongues of these animals with no associated pathology, whereas other isolates induce an acute immune response and are cleared rapidly (Schönherr et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Different isolates and strains of C. albicans vary significantly in the interactions that they establish with the host mucosa (Mandelblat et al, 2017;Schönherr et al, 2017). Experiments in mice have shown, for example, that independently of the source (e.g., bloodstream, OPC, or VVC), some C. albicans isolates can persist for a long time in the tongues of these animals with no associated pathology, whereas other isolates induce an acute immune response and are cleared rapidly (Schönherr et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between virulence and hemolysin production still needs to be further investigated and evaluated (Watanabe, 1999). On the other hand, all of the isolates in our study have revealed primarily the white-type colonies, which are reported to be more virulent than the opaque phenotype (Huang 2012;Mandelblat et al, 2017). White and opaque cells are different in terms of mating abilities and in the expression of many metabolic genes, indicating that these two types are adapted to various environments within a host (Tuch et al, 2010).…”
Section: Discussionmentioning
confidence: 76%
“…Interestingly, the source of the isolates did not seem to correlate with pathogenicity [ 10 ]. This was also true when strains were assessed in different experimental models [ 26 , 27 ]. In the OPC model, a high degree of damage induction by C. albicans strains correlated with strong inflammatory response and rapid fungal clearance, while strains inducing low epithelial cell damage triggered only a low degree of inflammation and in consequence colonized the host persistently [ 10 ].…”
Section: Host Responses To C Albicansmentioning
confidence: 97%